Correlation between Birth Length, Growth, and Development among Children in Rempoah Village Banyumas, Central Java, Indonesia - Sahda Vania Salsabiila; Qodri Santosa; Vitasari Indriani; Kurniawati Arifah; Joko Setyono (Faculty of Medicine Universitas Padjadjaran, 2021)
Background: The first 1,000 days of life are the foundation for growth and development of children in the next period. Birth length may represent growth and development during the intrauterine life. This study aimed to explore the correlation of birth length, growth, and development in children.Methods: This was analytic observational study with a cross-sectional design. Total sampling was taken, obtaining 368 children aged 6−60 months in several Integrated Service Post (Pos Pelayanan Terpadu, Posyandu), conducted from October to November 2018. Data were gathered from the book of Maternal and Child Health (Kesehatan Ibu dan Anak, KIA), including birth length, body length/height, and nutritional status using weight-for-length/height index. Data were analyzed by Spearman and Eta test. Results: Birth length was not correlated with nutritional status (p=0.108, r=0.084), but had a good correlation with body length/height (p=0.027, r=0.115) and development based on the KIA book (F calculated > F table, Ƞ=0.245).Conclusions: There is a correlation between birth length and body length/height as well as a correlation between birth length and development based on the KIA book. It is important for the community and health workers to monitor growth and development of children, by maximizing the use of KIA book.